Termination of Employment-Based on Efficiency in Indonesian Company - Kadek Agus Sudiarawan; Putu Edgar Tanaya; Kasandra Dyah Hapsari (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
The different interest between employer and employee is potentially causing Industrial Dispute between them. Industrial Disputes is dominated by Termination of Employment (laid off) dispute; one of the reasons is company efficiency. Based on that matter, it needs to be studied regarding its legality, procedure, employees’ rights and the pattern of Industrial Dispute Settlement regarding laid off through company efficiency. Based on these problems, several conclusions can be drawn. Firstly, Termination of Employment must be based on a valid reason under the law. Secondly, Termination of Employment due to company’s efficiency can only be done on the condition that the company permanently closed. Thirdly, in the case of termination of employment for company efficiency, the company must pay attention to the employee’s rights in the form of compensation based on consideration of wages and the employee’s duration of work. Fourthly, the pattern of Industrial Dispute Resolution that can be adopted by the parties is bipartite, tripartite and Industrial Relation Court.